Phase changes - Knight, James E.; Wickstrom, Lois; University of South Florida. Dept. of Chemistry; Human Relations Media, inc.; AIMS Media (Chatsworth, CA: AIMS Media)
Explores many questions about the different states of matter, including why water expands as it freezes while paraffin shrinks, why a person's breath fogs up a mirror, and how an iron anchor sinks right into a block of ice
Consultant, Gail Henson
Keywords: Matter; Phase transformations (Statistical physics)